Formula calculation methods of water content in sweet natural gas and their adaptability analysis - Zhu Lin; Fan Junming; Zhu Jia; Qin Li; Li Luling (Natural Gas Industry B, 2014)
Estimation of water content is the foundation of natural gas processing and designing, and a formula calculation method provides a solution simple and easy to be programmed by computers. In this regard, several main formula calculation methods of water content in sweet natural gas were reviewed and evaluated individually. There are formulas fitted with nomographic data (e.g. Sloan formula, Ning Yingnan formula, Khaled formula and Bahadori formula), empirical formulas fitted with experimental data (e.g. Zhu Lin formula, Behr formula and Kazim formula) and formulas generated based on water-hydrocarbon phases equilibrium (e.g. Saturated Vapor Pressure Model, Modified Ideal Model, Simplified Thermodynamic Model and Bukacek formula). The comparison of calculated and experimental values of each above formula calculation method indicates that, the Khaled formula provided the minimum average absolute deviation (AAD) – 2.524 0%, while the Behr method achieved the maximum AAD – 19.255%. After the analysis of the AAD results calculated by the methods at different temperature ranges, the Zhu Lin formula is recommended for −50 to −40 °C, the Sloan formula for −40 to 0 °C, the Simplified Thermodynamic Model for 0 to 37.78 °C, the Khaled formula for 37.78 to 171.11 °C, and the Bukacek formula for 171.11 to 237.78 °C.